2018
DOI: 10.1001/jamasurg.2017.5565
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and Facilitators of Implementing Enhanced Recovery Pathways Using an Implementation Framework

Abstract: IMPORTANCE Enhanced recovery pathways (ERPs) have the potential to reduce length of hospital stay, costs, and complications following surgery but can be challenging to implement. OBJECTIVE To examine the body of literature on ERPs to assess how authors describe barriers and facilitators of ERP implementation and identify, in aggregate, the best practices that should be considered utilizing the Consolidated Framework for Implementation Research (CFIR) to extract these elements and summarize common barriers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 71 publications
3
80
0
7
Order By: Relevance
“…This process of engagement was another important catalyst to instigate practice change, which relayed an initial positive effect onto EOF improvements as illustrated in Audit 3. The role of staff engagement and effective team communication has also been previously described as a necessary enabler for successful implementation of enhanced recovery programs …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This process of engagement was another important catalyst to instigate practice change, which relayed an initial positive effect onto EOF improvements as illustrated in Audit 3. The role of staff engagement and effective team communication has also been previously described as a necessary enabler for successful implementation of enhanced recovery programs …”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with previous literature that has emphasised the importance of staffrelated education to facilitate initiation of change and transition of practice prior to implementation of enhanced recovery programs. [11][12][13][14][15][16]20 As such, the present study included education sessions that described EOF guideline recommendations and descriptions of the nature and availability of local hospital diet codes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Any barriers to implementation should be identified, so that it can be determined locally what may delay further execution of the protocol. A thorough systematic review on ERAS implementation showed that there are multiple topics common to most institutions, even though the list of facilitators and barriers may vary considerably from one site to another . In general, lack of clear guidance was found to deter adherence, so standardization with some degree of flexibility to adapt the protocol to local factors is of paramount importance.…”
Section: Health System Considerations and Efficacy Of Eras Programsmentioning
confidence: 99%